Mycorrhizal Inoculation Differentially Affects Grapevine's Performance in Copper Contaminated and Non-contaminated Soils - Nogales, Amaia; Santos, Erika S.; Abreu, Maria Manuela; Arán, Diego; Victorino, Gonçalo; Pereira, Helena Sofia; Lopes, Carlos M.; Viegas, Wanda (Frontiers in Plant Science, 2019)
Plant inoculation with arbuscular mycorrhizal fungi (AMF) is increasingly employed to enhance productivity and sustainability in agricultural ecosystems. In the present study, the potential benefits of AMF inoculation on young grapevines replanted in pots containing vineyard soil with high Cu concentration were evaluated. For this purpose, one-year-old cv Touriga Nacional grapevines grafted onto 1103P rootstocks were further inoculated with Rhizoglomus irregulare or Funneliformis mosseae, or left non-inoculated, and maintained in a sterilized substrate under greenhouse conditions for three months. After this time, half of the plants were transplanted to containers filled with an Arenosol from a vineyard which had been artificially contaminated or not with 300 mg kg-1 of Cu. At the end of the growing season, soil nutrient concentration, soil dehydrogenase activity and mycorrhizal colonization rate were analyzed. Grapevine performance was assessed by measuring several vegetative growth and physiological parameters as well as nutrient concentrations in leaves and roots. In the non-contaminated soil, R. irregulare and F. mosseae-inoculated plants had significantly greater root biomass than the non-inoculated ones. However, the opposite effect was observed in the Cu contaminated soil, where non-inoculated plants performed better regarding shoot and root development. Concerning nutrient levels, an increase in Cu, Mg and Mn concentrations was observed in the roots of plants growing the contaminated soil, although only Mn was translocated to leaves. This led to a large increase in leaf Mn concentrations, which was significantly higher in non-inoculated and F. mosseae- inoculated plants than in the R. irregulare inoculated ones. Copper contamination induced a general decrease in leaf N, P and Fe concentrations as well as chlorosis symptoms. The largest decrease in N and P was observed in F. mosseae-inoculated plants, with 73 % and 31.2 %, respectively. However, these plants were the ones with the least decrease in Fe concentration (10% versus almost 30% in the other two inoculation treatments). In conclusion, this study indicates that soil Cu levels can modify the outcome of AMF inoculations in young grapevines, disclosing new AMF-plant associations potentially relevant in vineyards with a tradition of Cu-based fungicide application.